The Ethics of Refusal in Terrence Malick’s A Hidden Life - Marguerite La Caze; Magdalena Zolkos (Film-Philosophy)
Terrence Malick’s 2019 film A Hidden Life explores the ethical and political problem of refusal as an act and utterance of “not doing” violence and injustice that is expected. The film offers a nuanced and poetic depiction of Austrian peasant Franz Jägerstätter (1907–1943), who refused to give an oath of loyalty to Hitler (Führereid), and was subsequently imprisoned and executed under the Nazi laws criminalizing conscientious objection as an “offence of sedition.” We argue that Malick complicates the question of what it means to rise in defiance against power by locating Jägerstätter’s refusal not in religious dogma or a position of righteousness, but depicting it as a lived experience infused with affect, hesitation and doubt. We analyze the ethics and politics of refusal in A Hidden Life, focusing on the ways in which Malick depicts the possibility of leading an ethical life in an authoritarian state. This possibility concerns, first, the question of what alternatives emerge from the negative gestures of noncompliance, withdrawal or refusal and the question of enduring and, second, undergoing suffering, rather than imposing it on others. Situating our reading of Malick’s film in a philosophical dialogue with Michel Foucault’s writings on revolt and with Hannah Arendt’s reflections on responsibility in a dictatorship, we argue that Malick’s philosophy of refusal encompasses both the negative registers of refusal and articulates its affirmative, relational and testimonial dimensions in relation to history. This is because Malick's Jägerstätter undertook a very specific act of refusal – that of refusing to “make others suffer” (and chose instead to suffer himself). We conclude by drawing attention to three key presences in the film; nature, children and the wife, Fani, who turn the negative power of refusal into an affirmative gesture of companionship, co-presence and witnessing.